BUILDING INFORMATION MODELLING ADOPTION IN SMALL AND MEDIUM-SIZED ENTERPRISES: A BIBLIOMETRIC ANALYSIS REVIEW - Ismail, Elma Dewiyana; Ismail, Noor Akmal Adillah; Shapiai, Mohd Faiz (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This review paper analyses the knowledge composition of building information modelling (BIM) adoption and its application to small and medium-sized enterprises (SMEs). SMEs play an essential role in a country’s economy, as they contribute to employment, innovation, and economic growth. On the other hand, BIM is considered an advanced technology that improves the accuracy and efficiency of construction projects. BIM enables better project planning, execution, and management, minimising the impact on the environment and the waste of resources. This aligns with the sustainability goal of reducing energy consumption and maximising material utilisation. Through a bibliometric review, 239 articles were gathered from the Web of Science (WoS) repository. These publications were examined, and VOSviewer was used for visual mapping to identify themes and trends in the literature. The first analysis, bibliographic coupling, identified five clusters representing different themes within the research area. However, only 4 clusters were discussed, focusing on the most impactful themes. The second analysis, co-occurrence, consists of three main clusters that reveal the primary research areas. The integration of both analyses offers a profound understanding of BIM and SMEs. Furthermore, it emphasises the importance of awareness and education programs, technical support, and technological advancements to enhance BIM adoption. These findings can offer advantageous perspectives for practitioners and academics.